2021
DOI: 10.1136/jitc-2020-001136
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13 shapes immunoactive tumor microenvironment and enhances the efficacy of PD-1 checkpoint blockade in high-grade serous ovarian cancer

Abstract: BackgroundMost patients with high-grade serous ovarian cancer (HGSC) lack an effective response to immune checkpoint blockade, highlighting the need for more knowledge about what is required for successful treatment. As follicular cytotoxic CXCR5+CD8+ T cells are maintained by reinvigoration by immune checkpoint blockade in tumors, we attempted to reveal the relationship between CXCR5+CD8+ T cells and the tumor microenvironment to predict immunotherapy responses in HGSC.Methods264 patients with HGSC from two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(97 citation statements)
references
References 44 publications
2
94
0
1
Order By: Relevance
“…Gzma levels were increased, hinting to active NK cells. CT26-HER2 specimens showed an increase also in the cytokines that favor T cell activation ( Cxcl13 , Il2 , Il15 , Ccl5 , Ccl4 ) [ 39 ], in IFN-II and IFN-II-stimulated genes ( Ifng , Cxcl9 , Cxcl10 , Cxcl11 , Gbp2b , Stat1 , Irf1 ), in co-stimulatory genes ( Cd27 , Cd40lg ), in tumor necrosis factors ( Tnf , Fasl , Tnfsf18 , Tnfsf10 ), and in a global Th1-antitumor phenotype ( Tbet , MHC-II ), along with higher expression of inhibitory genes ( Pd1 , Pdl1 , Ctla4 , Lag3 , Ido2 , Havcr2 ). Increased expression of Ifng , Cxcl11 , Tnf , Tbet , and Pdl1 were in agreement with the flow cytometry and RT-PCR results ( Figure 4 I,J,L–N,P).…”
Section: Resultsmentioning
confidence: 99%
“…Gzma levels were increased, hinting to active NK cells. CT26-HER2 specimens showed an increase also in the cytokines that favor T cell activation ( Cxcl13 , Il2 , Il15 , Ccl5 , Ccl4 ) [ 39 ], in IFN-II and IFN-II-stimulated genes ( Ifng , Cxcl9 , Cxcl10 , Cxcl11 , Gbp2b , Stat1 , Irf1 ), in co-stimulatory genes ( Cd27 , Cd40lg ), in tumor necrosis factors ( Tnf , Fasl , Tnfsf18 , Tnfsf10 ), and in a global Th1-antitumor phenotype ( Tbet , MHC-II ), along with higher expression of inhibitory genes ( Pd1 , Pdl1 , Ctla4 , Lag3 , Ido2 , Havcr2 ). Increased expression of Ifng , Cxcl11 , Tnf , Tbet , and Pdl1 were in agreement with the flow cytometry and RT-PCR results ( Figure 4 I,J,L–N,P).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of CXCL13 in ICI therapy has been confirmed in vivo . Anti-PD-1 therapy failed in a CXCL13-null mouse model of BLCA, whereas the wild-type model showed a good response ( 59 ), and the treatment with a combination of CXCL13 and anti-PD-1 successfully retarded tumor growth in another mouse model of OV ( 60 ). Although the differences in CXCL13 secretion between CD4 + T cells and PD-1 hi CD8 + T cells remain elusive, these results indicate that CXCL13 is a potential therapeutic target that could be targeted in combination with ICI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the abundance of CD20 + B cells in ovarian cancer was only associated with improved prognosis in the presence of the TLS marker CXCL13. CD20 h i CXCL13 h i tumors had significantly longer overall survival and progression-free survival than the CD20 l o or CXCL13 l o counterparts ( Yang et al, 2021 ). Regulatory phenotypes may arise when B cells are scattered throughout the stroma and have substantial interaction with malignant ( Zhao et al, 2018 ) and TGFβ-producing cells, as suggested by the low T cell activity in immature TLSs ( Cabrita et al, 2020 ).…”
Section: Anti-tumor Role Of Tls B Cellsmentioning
confidence: 99%